Measurement of the serum level of Elabela for the early detection of acute kidney injury in hospitalized Iraqi COVID-19 patients - Gadhi, Maha H.; S. Saleh, Eman (Journal of the Faculty of Medicine Baghdad, 2022)
Background: Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) is caused coronavirus disease2019 (COVID-19) affecting people worldwide. The angiotensin converting enzyme2 (ACE2) represents areceptor of SARS-CoV-2 on the infected host cell. Apelin or its receptor agonists suppress the production ofangiotensin-converting enzyme (ACE) and angiotensin II (Ang-II) and is characterized by a protective effectagainst SARS-CoV-2.Objective: The study aims to assess the serum level of Elabela biomarker as an early detector for AcuteKidney Injury (AKI) in patients with COVID-19.Cases and Methods: This is a case-control study which included 45 hospitalized adult patients in multiplecenters (public hospitals) receiving COVID-19 cases in Baghdad. These cases had a positive real-time orreverse transcription polymerase chain reaction (RT-PCR) of nasal/oropharyngeal swabs. Excluded from thestudy were those with a negative PCR and comorbidities and 43 apparently healthy adult subjects as controls.The age range of the cases and controls was (20 to 60) yearsResult: There are no a statistically significant differences between the two groups in terms of age and genderdistribution. Statistically significant differences were found in terms of eGFR, S. Creatinine, D. dimer,NEU×103/µL, LYM×103/µL and ELA biomarker. Significant negative correlations were found betweenElabela with D. dimer and NEU×103/µL, and between eGFR with S. creatinine, D. Dimer, and NUT×103/µL.Conclusion: The Elabela biomarker can be used for the early detection of acute kidney injury in COVID-19patients.